Veterans in an unnamed war: Hidden abuse, truth-telling, resistance and recovery - Prescott Laura (Temida)
The author is the president and founder of Sister Witness International Inc a new organization of formerly institutionalized women, girls, and their allies. She is also a recovering addict, psychiatric expatient, and survivor of childhood abuse. The article is an edited version of a keynote address given at the 2nd annual convention of the International Society of Psychiatric Mental Health Nurses in Miami, Florida, on April 28, 2000.